SARAH GAVRON’S SUFFRAGETTE: SHAPING GENDER EQUALITY IN WOMEN’S RIGHT TO VOTE ISSUE (EUFONI: Journal of Language, Literary, and Cultural Studies, 2018)
This study aims to reveal the women struggle in fighting for human rights, especially for women done by women characters in a movie entitled Suffragette, directed by Sarah Gavron. As women who live the life whereas the government of the country is dominated by men, it is hard for women to participate in the government. Based on that, some research problems of this study are related to: (a) how society treat women especially related to women's working condition; (b) how is the oppression of women depicted in the movie; and (c) how is the First Wave of Feminism affects to the women movement. To analyze the movie, this study will use the conception of women's right by Mary Wollstonecraft and a perspective of First Wave of Feminism. The result of this study showed that the female characters want to shape women and men equality in the case of women’s right to vote as civil right. They wanted an equality between the men and the women, being appreciated, and had security from the country by become participant of government.Keywords: Suffragette, Gender Equality, Right to Vote, First Wave of Feminism, Mary Wollstonecraft.